2017
DOI: 10.5334/ijic.2520
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Collaboration between General Physicians and Emergency Department Teams in Belgium: A Qualitative Study

Abstract: This study aimed to assess interprofessional collaboration between general physicians and emergency departments in the French speaking regions of Belgium. Eight group interviews were conducted both in rural and urban areas, including in Brussels.Findings showed that the relational components of collaboration, which are highly valued by individuals involved, comprise mutual acquaintanceship and trust, shared power and objectives. The organizational components of collaboration included out-of-hours services, rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…Particularly, they were more likely to believe that, if necessary, their PCP informs the emergency physician of their arrival to the ED. Indeed, PCPs prefer to use this direct approach because it allows a direct interaction and case discussion between healthcare providers5 and helps to reduce waiting time for the elderly in the ED. At the same time, older people are shown to express greater satisfaction with the care received and have more realistic expectations 20.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Particularly, they were more likely to believe that, if necessary, their PCP informs the emergency physician of their arrival to the ED. Indeed, PCPs prefer to use this direct approach because it allows a direct interaction and case discussion between healthcare providers5 and helps to reduce waiting time for the elderly in the ED. At the same time, older people are shown to express greater satisfaction with the care received and have more realistic expectations 20.…”
Section: Discussionmentioning
confidence: 99%
“…First, ED activities in Brussels are three times more elevated than those in rural areas. In a previous study, actors from both levels of care have identified this workload as a major factor hindering communication and coordination between them 5. It has long been recognised that increasing access to general practitioners would decrease use of emergency services27–29 and that stronger primary care (in terms of accessibility, comprehensiveness and continuity) would lead to improved population health and lower healthcare service use 30.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations